Intravenous low dose clonidine premedication for attenuation of haemodynamic responses to laryngoscopy and endotracheal intubation - Kavi, Chandrashekarappa; CG, Ravindra; Mallappa, Kiran; AB, Kumara (International Journal of Research in Medical Sciences, 2017)
Background: Laryngoscopy and endotracheal intubation are almost always associated with an increased sympathetic activity. To attenuate the presser response, various drugs have been tried. This study aims at finding out if the low dose of clonidine (1.5µg/kg) is best suited for this purpose. Methods: This was a prospective study which involved two groups of patients. Each group had 30 patients who presented for elective, non-cardiovascular surgeries. The patients in group-C received Clonidine (1.5 µg/kg) and the patients in group-N received Normal saline. Heart rate (HR), Systolic blood pressure (SBP), Diastolic blood pressure (DBP) and Mean blood pressure (MBP) were recorded before and after intubation and at 1, 5, and 10 mins. The obtained clinical data were analyzed statistically with analysis of variance. Results: In our study, HR, SBP, and DBP and MBP all increased during intubation and thereafter in the control groups. Pretreatment with clonidine (1.5 μg/kg) significantly attenuated the cardiovascular and catecholamine responses to tracheal intubation Conclusion: Preoperative administration of a single dose of clonidine blunted the hemodynamic responses more than the placebo during Laryngoscopy and Intubation with reduced anesthetic requirements.